The time is now: antimicrobial stewardship in solid organ transplantation. Issue 4 (August 2021) - Hand, Jonathan M.
Abstract : Purpose of review: To provide a summary of complications of antimicrobials and opportunities for antimicrobial stewardship (AS) in solid organ transplant (SOT) patient care. Recent findings: Personalized, precision antimicrobial prescribing in SOT aiming to avoid negative consequences of antimicrobials is essential to improving patient outcomes. The positive impact AS efforts in transplant care has been recognized and bespoke activities tailored to special interests of transplant patients and providers are evolving. Strategies to optimize stewardship interventions targeting antibacterial, antiviral, and antifungal drug selection and dosing in the transplant population have been recently published though clinical integration using a 'handshake' stewardship model is an optimal starting point in transplant care. Other recent studies involving transplant recipients have identified opportunities to shorten duration or avoid antimicrobials for certain commonly encountered clinical syndromes. This literature, informing recent consensus clinical practice guidelines, may help support institutional practice guidelines and protocols. Proposals to track and report stewardship process and outcome measures as a routine facet of programmatic transplant quality reporting have been published. However, developing novel metrics accounting for nuances of transplant patients and programs is critical. Important studies are needed to evaluate organizational transplant prescribing cultures and optimal behavioral science-based interventions relevant to antimicrobial use in this population. Summary: Consequences of antimicrobial use, such as drug toxicities, and Clostridiodes difficile (CDI) and multidrug-resistant organisms colonization and infection disproportionately affect SOT recipients and are associated with poor allograft and patient outcomes. Stewardship programs encompassing transplant patients aim to personalize antimicrobial prescribing and optimize outcomes. Further studies are needed to better understand optimal intervention strategies in SOT.